Pengaruh Peningkatan Intensitas Latihan FutsalTerhadap VO2 Max - Dhewangga, Wisnu; , Wahyuni, SSt. FT, SPd, M. Kes (2014)
Background: VO2 Max is the maximum amount of oxygen in milli liters, which can be used in one minute per kilogram of body weight. People who have a good fitness values higher VO2 Max and can perform stronger activity than those who are not in good condition. One way that can be done to know the capacity of VO2 Max is the futsal training. Objective: To determine the effect of exercise intensity increases futsal against Vo2 Max Results: Respondents were 20 people given treatment of exercise intensity increases futsal. This research was carried out for 2 months with a frequency of 3 times in one week. Before being given treatment futsal training programmed, first of all respondents were measured VO2 Max (pre-test), after of exercise intensity increases futsal then measuring VO2 Max (Post test). In this study, respondents had increased levels of VO2 Max significant capacity can be indicated with a mean value for the pre-test of 35.41% and Post-test of 40.28%. Conclusion: It was concluded that there was an effect of exercise intensity increases futsal against Vo2 Max.